Transcatheter closure of atrial septal defect in children using the Occlutech Figulla occluder device - Mahmoud Ali; Amal El-Sisi; Hesham Salah El-Din; Sameh Bakhoum; Hossam Kandil (Wolters Kluwer Medknow Publications, 2017)
Background Percutaneous transcatheter closure of atrial septal defect (ASD) among children using devices other than the Amplatzer septal occluder has not been extensively tested. Objectives We evaluated the efficiency and safety of secundum ASD closure using the Occlutech Figulla ASD occluder in children and the efficiency and safety of secundum ASD closure under transthoracic echocardiography (TTE) guidance in children with less than 12 kg body weight. Patients and methods Forty-two patients (19 girls and 23 boys; mean age 4.8±2.0 years) were enrolled in a prospective cohort study. All patients underwent TTE and transesophageal echocardiography (TEE) to assess the characteristics of the ASD before transcatheter closure. Procedures were performed under fluoroscopic and TTE or TEE guidance. Follow-up was done at 1, 3, and 6 months following the procedure by clinical and TTE examination. Results The mean defect size was 14.9±4.2 mm on TTE and 16.1±4.7 mm on TEE. The mean device size was 17.9±4.9 mm (range 10.5-27 mm). The mean procedure time was 59.6±19.5 min. Thirty-one cases were performed under general anesthesia and TEE guidance, whereas the other 11 cases were performed under general anesthesia and TTE guidance. The device was placed successfully in all 42 patients. A small residual flow was seen immediately after device placement in three (7.1%) patients, which disappeared at 6 months. No complications occurred during the procedure. All patients were asymptomatic during the follow-up period. Conclusion Transcatheter closure of secundum ASD is generally safe and efficient in children younger than 12 years old, and ASD closure under TTE guidance in children less than 12 kg body weight is considered safe and efficient when performed in a tertiary center in the presence of an expert echocardiographer and interventional cardiologist.